Drug-Induced Liver Injury in Critically Ill Children Taking Antiepileptic Drugs: A Retrospective Study - Kannan Sridharan, MD, DM; Amal Al Daylami, MRCP; Reema Ajjawi, MD; Husain A.M. Al Ajooz, MD (Elsevier, 2020)
ABSTRACT: Background: Antiepileptic drugs are among the leading causes of drug-induced liver injury (DILI). Due to critical illness, children admitted to intensive care units are more prone to DILI. Objective: We attempted to elucidate the association between antiepileptic drug use and the associated factors resulting in DILI in a pediatric intensive care unit of a tertiary care hospital. Methods: We carried out an observational retrospective study on children receiving antiepileptic drugs. Details on their demographic characteristics, drugs, serum levels of antiepileptic drugs and liver function tests, and hospital stay were recorded. Council for International Organizations of Medical Sciences definitions were adhered to when defining DILI. LiverTox (https://livertox.nih.gov) and DILIrank were used to assess the risks of hepatotoxicity of the concomitant drugs. Regression models were developed for predicting DILI. Results: Five out of 9 patients taking phenobarbitone (55.6%), 9 out of 12 taking phenytoin monotherapy (75%), 7 out of 10 taking phenytoin/phenobarbitone (70%), all 3 receiving phenytoin/phenobarbitone/valproate sodium, and 1 with phenytoin/carbamazepine developed DILI either in the form of hepatocellular injury or liver biochemical test abnormalities. None of the patients had cholestatic or mixed type of liver injury. All the critically ill children received at least 2 concomitant drugs with hepatotoxic potential. Concomitant category B hepatotoxic drugs and toxic drug levels were significantly associated with increased risk of DILI. Similarly, a trend was observed for less-DILI-concern concomitant drug class and toxic drug levels when the drugs were analyzed by DILIrank classification. Conclusions: A significant proportion of critically ill children taking antiepileptic drugs experience DILI. Guidelines recommending use of drugs with reduced risk of potential hepatotoxicity for various concomitant disease states in such children admitted to intensive care units receiving antiepileptic drugs are urgently needed.